Echocardiographic Changes and Long-Term Clinical Outcomes in Pediatric Patients With Pulmonary Arterial Hypertension Treated With Bosentan for 72 Weeks: A Post-hoc Analysis From the FUTURE 3 Study - Beghetti, Maurice; Berger, Rolf M. F.; Bonnet, Damien; Grill, Simon; Lesage, Catherine; Lemarie, Jean-Christophe; Ivy, D. Dunbar (Frontiers in Pediatrics, 2021)
FUTURE 3 was a 24-week open-label, prospective, randomized phase 3 study that assessed the pharmacokinetics of bosentan 2 mg/kg b.i.d. or t.i.d. in children with pulmonary arterial hypertension (PAH). We report findings from a post hoc analysis that explored the prognostic value of echocardiographic changes during FUTURE 3 in relation to clinical outcomes observed during the 24-week core study and 48-week extension. Patients aged ≥3 months to <12 years (n = 64) received oral doses of bosentan 2 mg/kg b.i.d. or t.i.d. (1:1) for 24 weeks, after which they were eligible to enter the extension with continued bosentan administration. Echocardiographic evaluations were performed at baseline, Week 12 and Week 24 of the core study via central reading, and analyzed post hoc for correlation with clinical outcomes (time to PAH worsening, time to death, and vital status). Sixty-four patients were randomized in the core study (median [IQR] age 3.8 [1.7–7.8] years); 58 patients (90.6%) entered the 48-week extension. Most patients (68.8%) were receiving ≥1 PAH medication at baseline. Echocardiographic changes during the core study were small, with high variability. There were statistically significant associations at Week 24 between worsening of the parameters, systolic left ventricular eccentricity index (LVEIS) and E/A ratio mitral valve flow, and the outcomes of time to death and time to PAH worsening. Additional studies utilizing simple and reproducible echocardiographic assessments are needed to confirm these findings and, subsequently, allow identification of potential treatment goals in pediatric PAH.